Strengthening Consumer Experience In Digital Economy Development - Yuliana Cintya Jinus; Burhanudin Burhanudin (MediaTrend, 2023)
The development of the digital economy requires strengthening the consumer experience. This research was conducted by examining the relationship between digital economy security when shopping on ecommerce, output quality, customer utility, and the intention to recommend ecommerce to others. The survey was conducted at one of the ecommerce sites in Indonesia, namely Shopee, to test the above relationship and as many as 225 Shopee consumers were involved in the survey. The data collection method used in the study was to distribute questionnaires directly to the respondents. The collected data was then analyzed with a structural equation model. The results of the analysis show that digital economy security when shopping on ecommerce and output quality has a positive and significant effect on customer utility. Furthermore, customer utility has a significant positive effect on consumer recommendations. The results of this analysis indicate that ecommerce must always maintain transaction security and the quality of the output offered so as to provide utility to customers. This utility is important for the development of ecommerce because it encourages customers to recommend the ecommerce to other consumers.